Design topologies of a cmos charge pump circuit for low power applications - Rahman L.F.; Marufuzzaman M.; Alam L.; Mokhtar M.B. (MDPI AG, 2023)
Applications such as non-volatile memories (NVM), radio frequency identification (RFID), high voltage generators, switched capacitor circuits, operational amplifiers, voltage regulators, and DCDC converters employ charge pump (CP) circuits as they can generate a higher output voltage from the very low supply voltage. Besides, continuous power supply reduction, low implementation cost, and high efficiency can be managed using CP circuits in low-power applications in the complementary metal-oxide-semiconductor (CMOS) process. This study aims to figure out the most widely used CP design topologies for embedded systems on the chip (SoC). Design methods have evolved from diode-connected structures to dynamic clock voltage scaling charge pumps have been discussed in this research. Based on the different architecture, operating principles and optimization techniques with their advantages and disadvantages have compared with the final output. Researchers mainly focused on designing the charge pump topologies based on input/output voltage, pumping effi-ciency, power dissipation, charge transfer capability, design complexity, pumping capacitor, clock frequencies with a minimum load balance, etc. Finally, this review study summarizes with the discussion on the outline of appropriate schemes and recommendations to future researchers in selecting the most suitable CP design methods for low power applications. 2021 by the authors. Licensee MDPI, Basel, Switzerland.